Entender o passado e falar do presente: aportes a um Ensino Religioso descolonizador e pós-colonial = Understanding the past and talking about the present : contributions to a decolonizing and post-colonial Religious Education - Borges, Cristina (Numen, 2020)
The relationship between religion and education found in Religious School -RE a form of expression. And it has always been a subject of controversy for many years. Today, recognized and integrated to the National Common Curricular Base - BNCC (BRASIL, 2017) and having National Curriculum Guidelines (BRASIL, 2018) for initial teacher training, it is experiencing a unique moment. On the contrary, it does not mean that the problems have disappeared. The curricular issue remains a challenge in overcoming all forms of proselytism and coloniality, which still persists, mainly due to the long absence of specific training, today identified in the Sciences of Religion. Starting from a bibliographic review, the aim of the article is reflecting on the RE from the perspective of decoloniality and interculturality, placing it in the BNCC, with its competences and skills, for the construction of citizenship and a culture of peace as well as overcoming all form of intolerance and exclusion.